Inventering av järv 2022 - Mattisson, Jenny; Höglund, Linda; Hedmark, Eva; Brøseth, Henrik (2022)
The Norwegian Environment Agency (Miljødirektoratet) and the Swedish Environmental Protection Agency (Naturvårdsverket) have co-developed standard methodology and guidelines for the monitoring of wolverines in Scandinavia, that have been implemented in both Norway and Sweden since 2014. To estimate population size, and assess trends, wolverine reproductive areas (female territories) are annually surveyed during late winter and spring to register whether reproductions have occurred. The population size is estimated based on the number of wolverine reproductions that fulfil established criteria for documented or probable reproductions. The monitoring of wolverine reproductions, and registration of data into the shared database Rovbase, is conducted by field staff from the County Administration Boards CAB (Länsstyrelserna) in Sweden and the Norwegian Nature Inspectorate (Statens Naturoppsyn) in Norway. In Sweden, the Sami villages (administra-tive units for reindeer herding) assist the CABs by reporting presumed den sites, which can then be evaluated in the field by CAB field personnel. During the 2022 census, a total of 164 wolverine reproductions were registered in Scandinavia, which are four more than the year before (160 reproductions). Of these, 119 reproductions were found in Sweden and 45 in Norway. This corresponds to an increase of 19 reproductions (19%) in Sweden and a decrease of 15 reproductions (-25%) in Norway, compared to 2021. The model used to estimate population size, i.e., extrapolate number of reproductions to adult individuals in the population, accounts for annual variation in reproductive success by using a three-year floating average of the number of reproductions. Based on the number of wolverine reproductions during 2020-2022, the Scandinavian population size is estimated to 1019 adult wolverines (95% CI = 861–1282), defined as 1-year old or older, which is very similar to last year’s estimate. Of the 1019 wolverines, 351 wolverines (95% CI = 283–456) are estimated to be in Norway and 668 ...